2003
DOI: 10.1038/sj.ejcn.1601512
|View full text |Cite
|
Sign up to set email alerts
|

Effect of c-reactive protein and interleukins blood levels in postsurgery arginine-enhanced enteral nutrition in head and neck cancer patients

Abstract: Objective: It is known that the immune system is frequently affected in patients with head and neck cancer. Although immune dysfunction could be multifactorial, this immune system may be modulated by specific nutritional substrates, such as arginine. The aim of our study was to evaluate the effect of enteral nutrition supplemented with arginine on c-reactive protein (CRP), interleukin 6 (IL-6) and tumour necrosis factor (TNFa) in surgical head and neck cancer patients. Design: Randomized trial. Setting: Tertia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 22 publications
0
12
0
2
Order By: Relevance
“…There is evidence suggesting that enteral nutrition, supplemented with different agents including arginine and dietary fiber, improve immune function and reduce postoperative complications, in head and neck cancer patients (Van Bokhorstde van der Schueren et al, 2001) (De Luis et al, 2002). Our group (De Luis et al, 2003) did not find influence on interleukins blood levels with an arginine-enhanced enteral formula in a randomized clinical trial with two intervention groups. These groups have two differences in enteral formulas (arginine and fiber).…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…There is evidence suggesting that enteral nutrition, supplemented with different agents including arginine and dietary fiber, improve immune function and reduce postoperative complications, in head and neck cancer patients (Van Bokhorstde van der Schueren et al, 2001) (De Luis et al, 2002). Our group (De Luis et al, 2003) did not find influence on interleukins blood levels with an arginine-enhanced enteral formula in a randomized clinical trial with two intervention groups. These groups have two differences in enteral formulas (arginine and fiber).…”
mentioning
confidence: 56%
“…Our group (De Luis et al, 2003) showed no differences between two enteral formulas (arginine-and fiber-enhanced formula vs no arginine and no fiber formula) (De Luis et al, 2003). In this study, perhaps fiber could bias results, due to dietary fiber contained in arginine-enhanced formula and no in control group.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…It may be difficult to detect any effects on postoperative outcomes in trials conducted at a late stage of disease. Six trials came from one centre [2][3][4][5][6][7] and all trials had methodological limitations. The aspects of trial quality most consistently associated with treatment effect estimates were concealment of the allocation sequence and double blinding 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Ten randomised controlled trials published between 1999 and 2004 were identified with a total of 605 patients all undergoing surgery for head and neck for cancer (Tables 1 and 2) [2][3][4][5][6][7]11,16,18,20,21 . Additional unpublished data were obtained for the DE LUIS et al 2,3,5,6 and RISO et al 16 studies (these data contained methodology, patient characteristics, operation types and outcomes).…”
Section: Characteristics Of Trials Patients and Interventionsmentioning
confidence: 99%